2006
DOI: 10.1007/s11242-005-5049-z
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solutions to Multiphase First-Contact Miscible Models with Viscous Fingering

Abstract: In this paper, we analyze an empirical model of viscous fingering for three-component, two-phase, first-contact miscible flows. We present the complete range of analytical solutions to secondary and tertiary water-alternating-gas (WAG) floods. An important ingredient in the construction of analytical solutions is the presence of detached (nonlocal) branches of the Hugoniot locus, that is, curves in composition space that satisfy the Rankine-Hugoniot conditions but do not contain the reference state. We illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…This leads to a system of hyperbolic conservation laws, and the method of characteristics or the method of chromatography can be used to derive analytical solutions (e.g. [32,33,36,53,54,57]). As explained in the introduction, our primary interest is the mixing of the adsorbing but otherwise inert components (Fig.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…This leads to a system of hyperbolic conservation laws, and the method of characteristics or the method of chromatography can be used to derive analytical solutions (e.g. [32,33,36,53,54,57]). As explained in the introduction, our primary interest is the mixing of the adsorbing but otherwise inert components (Fig.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…This is relevant because solvent injection often leads to an unstable displacement process, in which the solvent fingers through, leading to a lower displacement efficiency. A rather extensive mathematical analysis of the effects of viscous fingering has recently presented in (Juanes and Blunt 2006) using the empirical viscous fingering model proposed by Blunt and Christie (Blunt and Christie 1993; …”
Section: Discussionmentioning
confidence: 99%
“…Eclipse results are shown with solid lines; streamline/front-tracking results are shown with dashed lines Christie 1994). The new analytical solutions presented in (Juanes and Blunt 2006) constitute the first step towards a complete Riemann solver for first-contact miscible flow in the presence of viscous fingering.…”
Section: Fig 19mentioning
confidence: 99%
“…MGF increases to 34% when the endpoint relative permeability of the gas phase is lowered to k o rg = 0.2, while it decreases to 16% when the endpoint relative permeability of the water phase is decreased to k o r w = 0.2. In (Juanes and Blunt 2006) it is shown that in WAG flooding with first-contact-miscible gas the optimal WAG ratio (equivalent to the MGF) is altered by viscous instability when a low viscosity gas pushes a higher viscosity oil out of the reservoir. A similar result could be obtained in fully compositional flow.…”
Section: Effect Of Relative Mobility On Mgfmentioning
confidence: 99%